Synergistic effect of renalase and chronic kidney disease on endothelin-1 in patients with coronary artery disease ‒ a cross-sectional study - Li, Yu-Hsuan (Sci Rep, 2018)
Endothelin-1 (ET-1) is associated with endothelial dysfunction and vasoconstriction. Increased circulating ET-1 levels are associated with long-term cardiovascular mortality. Renalase, released from kidney, metabolizes catecholamines and regulates blood pressure. An increase in circulating renalase levels has been reported in patients with chronic kidney disease (CKD) and is associated with coronary artery disease (CAD). We hypothesized the existence of a synergistic effect of serum renalase levels and CKD on ET-1 levels in patients with CAD. We evaluated 342 non-diabetic patients with established CAD. ET-1 and renalase levels were measured in all patients after an overnight fast. Patients with CKD had higher ET-1 (1.95 ± 0.77 vs. 1.62 ± 0.76 pg/ml, P < 0.001) and renalase levels (46.8 ± 17.1 vs. 33.9 ± 9.9 ng/ml, P < 0.001) than patients without CKD. Patients with both CKD and high renalase levels (>the median of 36.2 ng/ml) exhibited the highest serum ET-1 (P value for the trend <0.001). According to multivariate linear regression analysis, the combination of high serum renalase levels with CKD was a significant risk factor for increased serum ET-1 levels (regression coefficient = 0.297, 95% confidence interval = 0.063‒0.531, P = 0.013). In conclusion, our data suggest a synergistic effect of high serum renalase levels and CKD on increases in ET-1 levels in patients with established CAD.